2015
DOI: 10.1186/s12967-015-0439-7
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporins as diagnostic and therapeutic targets in cancer: How far we are?

Abstract: Aquaporins (AQPs) are a family of water channel proteins distributed in various human tissues, responsible for the transport of small solutes such as glycerol, even gas and ions. The expression of AQPs has been found in more than 20 human cancer types and is significantly correlated with the severity of histological tumors and prognosis of patients with cancer. More recent evidence showed that AQPs could also play a role in tumor-associated edema, tumor cell proliferation and migration, and tumor angiogenesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
111
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(114 citation statements)
references
References 108 publications
2
111
0
1
Order By: Relevance
“…Increased transcript levels of HsAQP1 , also sometimes accompanied by other aquaporins, have been commonly reported for cancerous cells1920, with the level of HsAQP1 expression often correlated with cell growth, grade of tumor2021, and metastasis2223. It has been also reported that the deletion of HsAQP1 was effective in reducing breast tumor size and lung metastasis23 and HsAQP1 silencing inhibited the proliferation and invasiveness of osteosarcoma cells24.…”
Section: Discussionmentioning
confidence: 94%
“…Increased transcript levels of HsAQP1 , also sometimes accompanied by other aquaporins, have been commonly reported for cancerous cells1920, with the level of HsAQP1 expression often correlated with cell growth, grade of tumor2021, and metastasis2223. It has been also reported that the deletion of HsAQP1 was effective in reducing breast tumor size and lung metastasis23 and HsAQP1 silencing inhibited the proliferation and invasiveness of osteosarcoma cells24.…”
Section: Discussionmentioning
confidence: 94%
“…10,17 Apart from its expected physiological functions, including urine concentration and exocrine gland secretion, as well as several unanticipated functions, including brain swelling, neural signal transduction, skin moisturization and fat metabolism, it has been implicated in tumorigenesis and tumor progression. 10,18 AQP3 has been found to be overexpressed in a wide variety of cancer types, and its overexpression has been demonstrated to be associated with tumor invasion, metastasis and poor survival.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have demonstrated that AQP5 promoted the proliferation and metastasis of CRC . Moreover, considerable clinical data suggest that high expression of AQP5 predicted tumor metastasis and poor prognosis of CRC . Nonetheless, the molecular mechanisms of AQP5 involved in CRC metastasis remain elusive.…”
Section: Introductionmentioning
confidence: 99%